Examining the Effects of Experimental/Academic Electroacoustic and Popular Electronic Musics on the Evolution and Development of Human–Computer Interaction in Music. - Meikle, George (Contemporary Music Review, 2016)
This article focuses on how the development of human–computer interaction in music has been aided and influenced by both experimental/academic electroacoustic art music and popular electronic music. These two genres have impacted upon this ever-changing process of evolution in different ways, but have together been paramount to the establishment of interactivity in music as we understand it today; which is itself having wide-ranging implications upon the modern-day musical landscape as a whole—both in the way that we, as listeners and audience members, purchase and consume music as well as conceptualise and think about it.